MG-FE PARTITIONING BETWEEN OLIVINE AND ULTRAMAFIC MELTS AT HIGH PRESSURES - Mibe K.; Fujii T.; Yasuda A.; Ono S. (My University, 2006)
Precise determination of the partitioning of Mg and Fe2+ between olivine and ultramafic melt has been made at pressures from 5 to 13 GPa using a MA-8 type multi-anvil high-pressure apparatus (PREM) installed at Earthquake Research Institute, University of Tokyo. A very short rhenium capsule (<100 ?m sample thickness) was adopted to minimize temperature variation within the sample container. Synthetic gels with the composition of the upper mantle peridotite were used as starting materials to promote the homogeneity. Analyses of quenched melts and coexisting olivines were made with an electron probe microanalyzer. The obtained partition coefficient, KD [=(FeO/ MgO)ol/(FeO/MgO)melt], decreases from 0.35 to 0.25 with increasing pressure from 5 to 13 GPa, suggesting a negative correlation between pressure and KD above 5 GPa. Our result is consistent with a parabolic relationship between KD and degree of polymerization (NBO/T) of melts reported by previous studies at lower pressures. The negative correlation between pressure and KD suggests that olivine crystallizing in a magma ocean becomes more Mg-rich with depth and that primary magmas generated in the upper mantle become more Fe-rich with depth than previously estimated. ? 2005 Elsevier Inc. All rights reserved.
Keywords: FRACTIONAL CRYSTALLIZATION; HIGH PRESSURE; MAGMA CHAMBER; MAGMA CHEMISTRY; SILICATE MELT